Karya Sastra Panji-Malat di Era Global - Budiarsa, I Wayan (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2025)
Panji literature, known in Bali as Malat, is a literary work classified as old prose that still exists amidst the onslaught of global culture. This literature has been adapted into various forms of art, including new prose literature in the form of novels. The Balinese people interpret and translate Malat into the Gambuh dance drama, which uses dialogue Kawi and Balinese. This article uses qualitative methods, with data collection involving observation, interviews, documentation, and literature review. The results indicate that Malat literature remains an integral part of Balinese Hindu life, both in the form of vocal art and the performing art "Gambuh," and is inseparable from religious rituals. Even in a global era marked by technological advancement, art derived from Panji/Malat literature remains relevant and serves as a means of uniting the Unitary State of the Republic of Indonesia (NKRI) and can also serve as a reference source for contemporary works.